A new species of Phyllopalpus Uhler (Orthoptera: Trigonidiidae) from Mexico - Figueroa, Jose Isaac; Ramos-Ortiz, Selene; Pineda, Samuel; Martínez, Ana Mabel; Palma-Castillo, Luis Jesús (Zootaxa, 2024)
A new species of the Sword-tailed Cricket genus Phyllopalpus Uhler (Trigonidiidae: Phylloscyrtini), from Tzitzio, in the Trans-Mexican Volcanic Belt, Michoacán, Mexico, is described and illustrated. Morphological and molecular data are integrated to describe Phyllopalpus nicolaita sp. nov. The new species is similar to Phyllopalpus caeruleus (Saussure) from Mexico, from which the color pattern of the body can distinguish it.